2011
DOI: 10.1615/jenvironpatholtoxicoloncol.v30.i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotection of Gentiana scabra Extract and Polyphenols in Liver of Carbon Tetrachloride-Intoxicated Mice

Abstract: In traditional Chinese medicine, the rhizomes of Gentiana scabra are used to treat hepatitis, stomatitis, and inflammatory diseases. This study aimed to examine the protective effects of G. scabra aqueous extract (GS) and polyphenols in liver of CCl4-intoxicated mice. Antioxidant activities of GS were also evaluated. Results showed that GS exhibited anti-lipid peroxidation, 2,2-diphenyl-1-picrylhydrazyl, and superoxide radical scavenging activities with IC50 values of 45.84, 183.38, and 56.25 μ/mL, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…1). This result is consistent with previously reported data [7]. In comparison with CCl 4 -injected groups, TJ-41 ?…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1). This result is consistent with previously reported data [7]. In comparison with CCl 4 -injected groups, TJ-41 ?…”
Section: Resultssupporting
confidence: 93%
“…Through these steps, necrosis is induced; this induction is termed as the fifth step. Multiple compounds have been reported to show protective effects against CCl 4 -induced hepatotoxicity, and associated protective mechanisms have been proposed to act on each of the five steps [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…1), which was consistent with previously reported data. 7) In contrast to the CCl 4 -injected group, pretreatment with JTX partially recovered food intake (from 1.18 to 2.96 g). In addition, saline-or JTX-injected groups showed the same level (5.32, 5.00 g, respectively) although dosage was about 8 times higher compared to the adult dose in human.…”
Section: Resultsmentioning
confidence: 88%
“…9) Several studies have shown how some compounds show protective effects against CCl 4 -induced hepatotoxicity. [7][8][9][10] Some of these compounds attenuated oxidative stress and the inflammatory response. 10) As JTX modulates the immune system, such as Toll-like receptor 4 signaling pathways, 25,26) it might also suppress the inflammatory response activated by CCl 4 .…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation